Geomorphological Analysis Methodologies for Houran Valley Basin in Iraq - aldayyeni, Maryem; A. Jawad, Laith (Iraqi Journal of Physics, 2023)
Extracting, studying and interpreting the morphological database of a basin is a basic building block for building a correct geomorphological understanding of this basin. In this work, Arc GIS 10.8 software and SRTM DEM satellite images were used. The principle of data integration was adopted by extracting the quantitative values of the morphometric characteristics that are affected by the geomorphological condition of the studied basin, then eliciting an optimal conception of the geomorphological condition of the basin from the meanings and connotations of these combined transactions. Hypsometric integration was extracted for each region in the basin separately with the value of integration of the plot curve for the relative heights of the basin regions with their respective regions.  Hypsometry coefficients reveal that regions (A, B, C, D, and F) are still in their formative years, while region E is in the maturity stage and region G is in the monadnock stage of the geomorphological cycle.